Room temperature fiber optic gas sensor technology based on nanocrystalline Ba3 (VO4)2: Design, spectral and surface science. (November 2019) - Subramanian, M.; Violet Dhayabaran, V.; Shanmugavadivel, M.
Graphical abstract: Highlights: Nano sized Ba3 (VO4 )2 was synthesized by surfactants assisted solution combustion method. Ba3 (VO4 )2 clad-modified Fiber optic sensor was completely operates at room temperature. The Ba3 (VO4 )2 nanomaterial was found to be more sensitive to ammonia and ethanol even at low concentration level (50 ppm). Abstract: Large yields of barium vanadium oxide nanopowder were obtained by surfactant mediated solution combustion method. The structural characterization and morphological studies were done by X-ray diffraction, scanning electron microscope, transmission electron microscope, FT-IR spectra and diffuse reflectance spectra (DRS). The fiber optic gas sensing properties of the synthesized nanomaterial were tested with volatile organic compounds (VOCs) such as, ammonia, acetone, methanol and ethanol. The results reveal that nanocrystalline Ba3 (VO4 )2 has the highest sensitivity to ammonia and ethanol with a fast response and a recovery time of 52 and 61.5 min, respectively.